DYNAMIC SIMULATION OF DUAL-CREDIT POLICY IN THE AUTOMOBILE INDUSTRY OF CHINA USING THE BASS MODEL - He, Qing; Zhao, Hua (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
As a crucial emerging policy for the Chinese automotive industry to achieve energy saving and emission reduction as well as to promote the development of new energy vehicles (NEVs), the dual-credit policy has attracted considerable attention from scholars since its implementation. Nonetheless, the specific implementation outcomes have been less than satisfactory, necessitating further improvements. This paper establishes a prediction model based on the principles of the dual-credit policy and the core parameter of automobile sales using the Bass model as the system, thereby constructing a complex dynamic system composed of three subsystems to explore the effects of adjusting specific credit standards. The research findings are as follows: (1) In the initial years of policy implementation, the selection of different credit standards has little impact on the credit market. Only after more than 5 years, the differences become increasingly apparent. It is recommended that the government should persist in dynamically adjusting the credit policy. (2) Strict credit policies have a certain promoting effect on the proportion of new energy vehicles and their driving range capabilities. (3) This policy has limitations on the energy-saving and emission-reduction effects of traditional fuel vehicle enterprises.